Kinematic Gait Impairments in Children with Clubfeet Treated by the Ponseti Method: A Systematic Review and Meta-Analysis - Lianne Grin; Lisa van Oorschot; Benedicte Vanwanseele; Saskia D. N. Wijnands; H. J. J. (Cojanne); Arnold T. Besselaar; M. C. (Marieke) (MDPI AG, 2023)
Background: Being aware of possible gait impairments in Ponseti-treated clubfoot children might be useful for optimizing initial and additional treatment. Therefore, this systematic review and meta-analysis aimed to identify kinematic gait abnormalities in children with clubfoot treated with the Ponseti method (with and without relapse). Methods: A systematic search was conducted. Studies comparing kinematic gait parameters of Ponseti-treated clubfoot children to healthy controls were included. Meta-analyses and qualitative analyses were conducted on the extracted data. Results: Twenty studies were identified. Twelve of the 153 reported kinematic outcome measures could be included in the meta-analysis. Plantarflexion at push-off, maximum ankle dorsiflexion during the swing, maximal plantarflexion, and ankle range of motion was significantly lower in Ponseti-treated clubfoot children. Ponseti-treated clubfoot children showed more internal foot progression. Qualitative analysis revealed 51 parameters in which pre-treatment relapse clubfeet deviated from healthy controls. Conclusions: Ponseti-treated clubfoot children showed several kinematic gait differences from healthy controls. In future studies, homogeneity in measured variables and study population and implementation of multi-segmental foot models will aid in comparing studies and understanding clubfoot complexity and treatment outcomes. The question remains as to what functional problems gait impairments lead to and whether additional treatment could address these problems.